Production and marketing of cretan olive oil and wine - Nikolaidis A. (Strengthening endogenous development patterns in European agriculture, 1993)
This paper presents some significant results from the market of two Cretan agricultural products, olive oil and wine, using an original expert decision support system. The first sections deal respectively with the production of olive oil and wine in Greece. The research methodology is outlined and preliminary results from its application in the Greek market are also presented.
Seminar on 'Strengthening Endogenous Development Patterns in European Agriculture', 1992/10/20-22, Chania (Greece)